2006
DOI: 10.1016/j.jacc.2005.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Early Inflammation and Risk of Long-Term Development of Heart Failure and Mortality in Survivors of Acute Myocardial Infarction

Abstract: C-reactive-protein is a marker of long-term development of HF and mortality in patients with acute MI and provides prognostic information beyond that provided by conventional risk factors and the degree of left ventricular systolic dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
186
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(207 citation statements)
references
References 37 publications
15
186
2
4
Order By: Relevance
“…Similar results were reported by other authors (11)(12)(13)(14)(15). Researches showed that there is a significant correlation between the CRP with an increased risk of cardiovascular death.…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported by other authors (11)(12)(13)(14)(15). Researches showed that there is a significant correlation between the CRP with an increased risk of cardiovascular death.…”
Section: Discussionsupporting
confidence: 90%
“…The present study demonstrated a statistically significant difference in mean hs-CRP concentrations among patients with different Killip classes (0.62 mg/dl in Killip class I vs. 0.98 mg/ml in Killip class IV; P<0.05). This finding also supports an earlier study by Suleiman et al (19), in which it was reported that patients with acute MI had CRP levels in the upper quartile, were older, had higher baseline creatinine levels and had a greater history of heart failure.…”
Section: Hs-crp (Mg/dl) Hs-trop T (Ng/ml) ---------------------------supporting
confidence: 91%
“…According to a study published by Bonvini et al, inflammatory response following an acute myocardial infarction should CRP is an acute-phase protein synthetized by hepatocytes under the control of inflammatory cytokines and particular intrerleukin 6, and is released into the circulation in response to inflammation and tissue damage. Given that the circulating level of CRP, considered currently considered to represent a "golden marker for inflammation", reflects the severity of inflammatory response and plays a significant role in the development of atherosclerosis, many studies have attempted to predict the future cardiovascular events and the response to therapy based on CRP-based risk classification (14,15). It has been proved that high levels of circulating CRP upon admission correlates with the extent of the infarction, the development of postinfarction heart failure and the presence of severe lesion by angiography, while in patients undergoing primary PCI, high CRP level before the procedure predicted the rate of early complications (16,17).…”
Section: Discussionmentioning
confidence: 99%